AN EVALUATION OF ENGLISH SPEAKING ACCELERATION PROGRAM AT IKIP PGRI PONTIANAK - Irwan, Dedi (Jurnal Pendidikan Bahasa, 2014)
This research aimed at finding out the discrepancy existing between the program standard criteria of English speaking acceleration program and its implementation. In order to run the evaluation, program evaluation was implemented at this research, while the model used was the Provus’ discrepancy model. The research subjects involved were the stakeholders in charge at this program such as the key people in charge, program staffs, lecturers and program participants. The program implementation discrepancy was investigated by measuring the discrepancy at program input implementation, program process implementation and program output implementation. Program output variable was investigated from two aspects: interim output and terminal output. The data analyzing technique used was qualitative analysis enhanced by the quantitative measurement. The findings of this research are the program standard criteria and discrepancy score for the input implementation, process implementation and output implementation of the program. The implementation of input criteria is 81.33%, the process criteriais 4.77% and at the ultimate output is 85%. The terminal output evaluation finds the improvement of vocabulary mastery level up to 22.28%, the improvement of speech accuracy is 31.37% and the improvement of the pronunciation is 29.9%. Besides, it is also found that the decrease of the word rate from 2.095 at the pretest which falls to 1.939 at the posttest. Keyword: Program evaluation, Provus’ discrepancy approach, English speaking acceleration program.